2019
DOI: 10.3389/fmicb.2019.00270
|View full text |Cite|
|
Sign up to set email alerts
|

Inference of Convergent Gene Acquisition Among Pseudomonas syringae Strains Isolated From Watermelon, Cantaloupe, and Squash

Abstract: Pseudomonas syringae sensu stricto (phylogroup 2; referred to as P. syringae ) consists of an environmentally ubiquitous bacterial population associated with diseases of numerous plant species. Recent studies using multilocus sequence analysis have indicated the clonal expansion of several P. syringae lineages, located in phylogroups 2a and 2b, in association with outbreaks of bacterial spot disease of watermelon, cantaloupe, and squash in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…Biological diversity within an ST (two strains of X. fastidiosa subsp. multiplex ST7 were shown to have different host ranges under experimental conditions) was recently demonstrated on X. fastidiosa (Nunney et al, 2019) and this is generally observed for other bacterial pathogens (Jaureguy et al, 2008;Nicolas-Chanoine et al, 2014;Newberry et al, 2019). In addition, generation of novel strains with specific host range has been evidenced for X. fastidiosa (Nunney et al, 2014b).…”
Section: Taxonomic Level In Phytosanitary Measuresmentioning
confidence: 72%
“…Biological diversity within an ST (two strains of X. fastidiosa subsp. multiplex ST7 were shown to have different host ranges under experimental conditions) was recently demonstrated on X. fastidiosa (Nunney et al, 2019) and this is generally observed for other bacterial pathogens (Jaureguy et al, 2008;Nicolas-Chanoine et al, 2014;Newberry et al, 2019). In addition, generation of novel strains with specific host range has been evidenced for X. fastidiosa (Nunney et al, 2014b).…”
Section: Taxonomic Level In Phytosanitary Measuresmentioning
confidence: 72%
“…It forms a REG with HopC1 in P. syringae pv. tomato DC3000 during Arabidopsis infection (Wei et al, 2007), indicating a similar role in virulence, and is often clustered with this effector physically on the genome (Baltrus et al, 2012;Newberry et al, 2019). Although the four highlighted effectors appear to have important roles in virulence, further functional characterization is required to support the in silico predictions.…”
Section: T3es Promoting Virulence?mentioning
confidence: 99%
“…A host specificity study on cucurbits showed remarkable variation in the virulence of phylogroup 2 strains on two different host species (Newberry et al, 2019), which was postulated to be due to differences in effector repertoires. Another study by Rezaei and Taghavi (2014)…”
Section: Diverse Weaponry Leads To Pathogenicitymentioning
confidence: 99%
See 2 more Smart Citations